Beneficial Role of Silicon on Regulating C, N, and P Stoichiometric Homeostasis and the Growth of Sugarcane Seedlings under Aluminum Toxicity - da Silveira Sousa Junior, Gilmar [UNESP]; Hurtado, Alexander Calero [UNESP]; de Souza Junior, Jonas Pereira [UNESP]; de Mello Prado, Renato [UNESP]; de Cássia Piccolo, Marisa; Dos Santos, Durvalina Maria Mathias [UNESP] (Springer Nature, 2022)
This study investigates the protective role of silicon (Si) on growth performance, nutrient homeostasis, and C:N:P stoichiometric of sugarcane (Saccharum spp.) seedlings under aluminum (Al) stress in hydroponic conditions. Experiments were conducted as a factorial scheme (2 × 2) in a randomized complete block design (RCBD), with four replications, for each sugarcane cultivar (“CTC9002” and “CTC9003”). They were grown in pots filled with normal Clark nutrient (pH = 5.8 without Al) and acidic Clark nutrient solution (pH = 4.5 with 15 mg L−1 of Al, as aluminum sulfate [Al2 (SO4)3·18H2O]) in the absence or presence of Si (2 mM, as potassium silicate (K2SiO3). Sugarcane seedlings of both cultivars grown under Al stress alone significantly decreased root, culm, and leaf dry biomass, and this adverse effect was reversed by Si supplementation. Added Si also modified nutrient homeostasis of both sugarcane cultivars, and these effects varied depending on plant organs. Si decreased the concentration of C, N, and P and correspondingly increased C:N, C:P, and N:P stoichiometric. In addition, both sugarcane cultivars had a positive response to Si supplementation, but cultivar “CTC9003” is more recommended under added Si to ameliorate the detrimental effects caused by Al toxicity. The findings of this study indicate that Si promoted attenuation of Al-stressed sugarcane seedlings by regulating nutrient and homeostasis stoichiometric, leading to improve dry biomass production.
Keywords: Ecological Stoichiometric; Nutrient Homeostasis; Plant Organs; Saccharum officinarum; Silicon